ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN/KOTA PROVINSI JAWA TENGAH TAHUN 2008-2012 (Students' Journal of Accounting and Banking, 2014)
This study aimed to examine the effect of GDP, inflation, population and the hotel and restaurant tax to the Local Revenue (PAD) in the District / City of Central Java Province. This study aimed to examine the effect of GDP, inflation, population and the number of hotel to the Local Revenue (PAD) in the District / City of Central Java Province. In this study population used was the whole area in the district / city of Central Java province in 2008-2012. This data is taken from BPS Central Java. The sampling technique using purposive sampling. Mechanical testing data is to use a multiple linear regression analysis. The analysis showed that the variables GDP and Number of Hotels as the independent variables have a significant influence and inflation has a significant negative effect on the Local Revenue. While the variable Population has no significant effect on the Local Revenue. Keywords: PAD, GDP, Inflation, Population, Number of Hotels